Hippocampal volume reduction and autobiographical memory deficits in chronic schizophrenia - Herold, Christina; Lässer, Marc; Schmid, Lena A.; Seidl, Ulrich; Kong, Li; Fellhauer, Iven; Thomann, Philipp; Schröder, Johannes (Psychiatry research, 2013)
Although autobiographical memory (AM) deficits and hippocampal changes are frequently found in schizophrenia, their actual association remained yet to be established. AM performance and hippocampal volume were examined in 33 older, chronic schizophrenic patients and 21 healthy volunteers matched for age, gender and education. Psychopathological symptoms and additional neuropsychological parameters were assessed by using appropriate rating scales; magnetic resonance imaging (MRI) 3-T data were analyzed via an automated region-of-interest procedure. When compared with the control subjects, patients showed significantly decreased left anterior and posterior hippocampal volumes. Episodic but not semantic AM performance was significantly lower in the patients than in the healthy controls. Both episodic and semantic AM deficits were significantly correlated with volume of the left hippocampus in the patient group. In contrast, deficits in verbal memory, working memory and remote semantic memory observed in the patients did not relate to hippocampal volume. Our findings indicate that AM deficits in chronic schizophrenia are associated with hippocampal volume reductions and underline the importance of this pathology in schizophrenia.